Dynamic Systems and Control, Parts a and B 2005
DOI: 10.1115/imece2005-80508
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative, Experimental Study of Model Suitability to Describe Vehicle Rollover Dynamics for Control Design

Abstract: This work presents results of an initial investigation into models and control strategies suitable to prevent vehicle rollover due to untripped driving maneuvers. Outside of industry, the study of vehicle rollover inclusive of both experimental validation and practical controller design is limited. The researcher interested in initiating study on rollover dynamics and control is left with the challenging task of identifying suitable vehicle models from the literature, comparing these models with experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Therefore, we conclude that the tire feature and road selfaffine characteristics have a significant effect on both the C.G acceleration at limitation station with different loads under the combined steering and braking maneuver situations. Meanwhile, it is noticeable that the dynamic variation trend of C.G acceleration is consistent with the corresponding tire force, which are the leading factors that predominate the C.G acceleration (according to (14) and (15)), respectively.…”
Section: The Cg Acceleration Difference Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, we conclude that the tire feature and road selfaffine characteristics have a significant effect on both the C.G acceleration at limitation station with different loads under the combined steering and braking maneuver situations. Meanwhile, it is noticeable that the dynamic variation trend of C.G acceleration is consistent with the corresponding tire force, which are the leading factors that predominate the C.G acceleration (according to (14) and (15)), respectively.…”
Section: The Cg Acceleration Difference Characteristicsmentioning
confidence: 91%
“…Some vehicle dynamic models such as 2 DOF and 3 DOF [14] were established to analyze the vehicle rollover, but no model is found to be fully satisfactory in accuracy which is used to predict the vehicle yaw rate and vehicle lateral acceleration simultaneously. About tire forces estimate [15][16][17][18], estimation method of tire forces and the dynamic states is employed to discuss the vehicle stability control and the influence on run-off-road risk.…”
Section: Introductionmentioning
confidence: 99%
“…The full-sized vehicle is equipped with a high-accuracy Novatel SPAN L1/L2 global positioning system factory integrated with a Honeywell HG1700 inertial navigation system to measure the states of the vehicle. The parameter values for the full-sized vehicle are summarised in Table 3, and details on the measurement of these parameters can be found in the literature [55,56]. The parameter definitions are consistent with those previously given in Table 2.…”
Section: Dimensionless Parametersmentioning
confidence: 97%
“…In previous full-sized vehicle studies within our research group [55,56], it has been shown that the tire-lag phenomenon significantly influences the dynamics of the full-sized vehicle, especially the phase of the frequency responses. Since, in this work, dynamic behaviours are compared between the full-sized and scaled vehicles, the effects of the tire lag must also be considered in the vehicle dynamic models.…”
Section: Tire-lag Dynamicsmentioning
confidence: 99%
“…e-mail: sungmo.yang@renaultsam-sungM.com K β : angular spring coefficient of body yaw C ij : ij's suspension damping rate C β : angular damping rate of body yaw K SR : ratio of steering wheel and tire wheel F tx_ij , F ty_ij , F tz_ij : ij's tire force of x-, y-, and z-direction based on each tire coordinate (x t , y t , z t ) (Bergman, 1965;Allen et al, 1986). However, since 1980, the dramatic development of computers has accelerated many studies through not only simple low-order models using a Newtonian approach (Abe, 1994;Cameron and Brennan, 2005) but also multibody complex equations that are mainly used in commercial software such as RECURDYN and ADAMS. Consequently, it may be more useful to discuss interesting phenomena in terms of what types of existing equations or tools will be applied rather than what idea will be created to understand them.…”
Section: Nomenclaturementioning
confidence: 98%